Faire de la recherche en marge ou s’en tenir aux marges de la recherche - Camille Boutron (Sociologies, 2024)
This article examines the effects of the restructuring of academia on the individual trajectories of social science researchers. It shows that beyond the precariousness and the difficulty of accessing a permanent position, knowledge production has been considerably affected by the market-based logic imposed by the neoliberal policies over the last fifteen years in France and elsewhere, contributing to the reproduction of relations of oppression and domination. Based on a personal experience and assuming its testimonial dimension, this article above all wants to be reflexive and committed to change.